FASHION OUTLET DESIGN WITH THE THEME OF LOCAL PRIDE AS AN EFFORT TO DEFEND NATIONAL PRODUCTS - Pahlawan, Muhammad Reiza; Elviana, Eva (Border: Jurnal Arsitektur, 2020)
The economic improvement in the fashion sub-sector was contributed by local small and medium business (SME) brand owners engaged in the fashion sector. Local Pride Movement is a movement to support local brands that will foster the interest of Indonesian people to look at domestic fashion brands. Bandung as Parijs Van Java in Indonesia, produces many local fashion brands, known as the founders of fashion factory outlets (FOF), which are fashion tourism destinations. However, this FOF began to decline with the 4.0 industrial revolution, where shopping was done online, so many home industries did not have a place to display their merchandise. To keep up with online shopping trends, Fashion Outlets are needed that specialize in local brands, with the aim of promoting and increasing the sale and purchase of local industries. The design of this Fashion Outlet uses the theme of Local Pride with the approach of Contemporary Architecture, which elevates the Art Deco style in the current era. Contextualism design method, namely aligning the appearance of the building with the context of the surrounding environment, with the International Style style. The results of the design concept are containers with a variety of atmosphere and local fashion brand shopping experience, such as Shopping Street, Thrifting Market (buying and selling used goods), Indoor Retail, Event and Food Market Floor which is equipped with Local Culinary Stand, auction room and temporary gallery, and Rooftop Retail which is outdoor space on the upper floor.